The subplacenta of the red-rumped agouti (Dasyprocta leporina L) - dos Santos Tatiana; Ambrosio Carlos; Carter Anthony M; Rodrigues Rosangela; Miglino Maria (BMC, 2006)
Abstract Background Hystricognath rodents have a lobed placenta, comprising labyrinthine exchange areas and interlobular trophoblast. These correspond to the labyrinthine and spongy zones of other rodent placentae. Beneath them, however, is a structure unique to hystricognath rodents called the subplacenta. We here describe the subplacenta of the red-rumped agouti and examine the possible functional correlates of this structure. Methods Placentae were collected from early in midgestation to near term of pregnancy and examined by standard histological techniques, immunohistochemistry and transmission electron microscopy. In addition, to study the microvasculature of the subplacenta, vessel casts were inspected by scanning electron microscopy Results In the subplacenta, lamellae of connective tissue support a layer of mononuclear cytotrophoblast cells. Beneath this is found syncytiotrophoblast. Clusters of multinuclear giant cells occur in the transition zone between the subplacenta and decidua. There are prominent intercellular spaces between the cytotrophoblast cells. The basal membrane of these cells is often close to fetal blood vessels. The syncytiotrophoblast surrounds an extensive system of lacunae. Microvilli project into these lacunae from the plasma membrane of the syncytiotrophoblast. The syncytial cytoplasm contains electron-dense granules. This is probably the amylase-resistant PAS-positive material identified by histochemistry. The subplacenta is supplied entirely from the fetal circulation. Within it the vessels pursue a tortuous course with sinusoidal dilatations and constrictions. Conclusion The functions that have been attributed to the subplacenta include hormone production. Our findings are consistent with this interpretation, but suggest that hormone secretion is directed towards the fetal circulation rather than the maternal tissues.